A justiça de transição na perspectiva do direito internacional dos direitos humanos: a garantia da justiça e da paz no acordo entre o Estado colombiano e as FARC-EP - Pereira, Felipe Tôrres (2019)
For more than five decades, the Colombian state has been fighting non-international armed conflict with groups of guerrilla and paramilitary origins, clashes that have already produced millions of victims with social, political, economic and cultural implications for the Colombian state and society. In 2012, the government initiated pacification dialogues with the Revolutionary Armed Forces of Colombia - People's Army (FARC-EP), which prompted the conclusion of a peace agreement between the parties in September 2016. Congress approved the compromise, after the rejection in popular consultation, in November of that year, and, since then, measures have been adopted for its implementation. It is a complex and controversial compromise and one of the most discussed points concerns is the guarantee of justice. Special strategies were envisaged, such as granting amnesties, applying restorative sanctions to those responsible for serious human rights violations and the selection and prioritization of some cases, measures aimed primarily at ensuring justice and an allegedly long lasting and stable peace. The legality and legitimacy of transitional justice instruments, as in the Colombian case, require their compatibility not only with domestic norms, but also with international norms applicable to the subject. In this sense, this study aims to verify whether these institutes are compatible with international human rights law, with emphasis given to the Inter-American Human Rights System (IAHRS), of which the Colombian State is a member. Using an inductive approach and interpretative and historical methods applied to bibliographic (books and journal articles) and documentary (treatises, positions and decisions of international bodies) sources, this study is developed in four sections. The first one covers the internal armed conflict in Colombia, based on considerations of the rules applicable to internal conflicts and the characterization and contextualization of the conflict and peace process with the FARC-EP. After that, we carry out a theoretical research on transitional justice, in order to understand its meaning, the assumptions, and the implications for the state, and then, in the third section of development, we analyze transitional rights, paying particular attention to the right to justice. Finally, in the fourth part of this study, we investigate whether and to what extent amnesties, sanctions against perpetrators of violations of rights and the selection and prioritization of cases provided for in the peace agreement between Colombia and the FARC-EP are compatible with the human rights standards adopted in this analysis. It is concluded that, with the exception of case prioritization, the analyzed institutions have no express and uncontroversial understanding within the scope of the IAHRS. The parameters of the Inter-American Court of Human Rights and the positions of the Inter-American Commission on Human Rights make it easier to support the compatibility of amnesty, the modalities of sanctioning perpetrators of serious human rights violations, and the prioritization of cases with the American Convention on Human Rights, in contrast to case selection. However, in this study, it is argued that all the institutes, in their theoretical sense, are consistent with this treaty, and therefore they are instruments to make justice compatible with the pacification of the internal conflict.